A Comparison of "Girls’ Education" in the Discourse of the Supreme Leader and the Fundamental Transformation Document of Education - Mohammadali Mlipoor (پژوهش در آموزش معارف و تربیت اسلامی, 2024)
Girls’ education entails outlining a special educational path for girls that aligns with their future maternal role. This study aims to compare the concept of girls’ education as presented in the discourse of the Supreme Leader (Ayatollah Khamenei) and the Fundamental Transformation Document of Education to identify the strengths and weaknesses of the latter. Employing a descriptive-analytical method, the findings reveal that the treatment of girls’ education in the Fundamental Transformation Document is vague. In contrast, the Supreme Leader’s statements provide numerous instances emphasizing the societal importance of motherhood. Understanding this position fosters enthusiasm among girls for taking on the role of motherhood, harmonizing with their innate disposition in the near future. In his discourse, the Supreme Leader defines homemaking as a crucial factor in education, considering mothers as the key to raising virtuous children. Additionally, the Supreme Leader’s discourse outlines pathways to realizing motherhood as a vocation, including valuing women’s work within the home and discouraging the separation of mothers from their children. Similarities between the Fundamental Transformation Document and the Supreme Leader’s statements include the distinct role of girls and the emphasis on motherhood. Differences lie in the detailed articulation of the maternal role and the conditions for its realization, as elaborated in the Supreme Leader’s statements but lacking in the document.